Dicey's song - Voigt, Cynthia (New York : Simon Pulse, 2002)
Now that the four abandoned Tillerman children are settled in with their grandmother, Dicey finds that their new beginnings require love, trust, humor, and courage.
Sequel to: Homecoming.
Accelerated Reader AR
Cynthia Voigt is a Maine author. She has been a resident of Deer Isle since the 1990s.
Keywords: Brothers and sisters -- Fiction; Families -- Fiction; Young adult fiction; Domestic fiction